2019
DOI: 10.1002/mrm.27872
|View full text |Cite
|
Sign up to set email alerts
|

Partial volume correction for quantitative CEST imaging of acute ischemic stroke

Abstract: Purpose Contributions of cerebrospinal fluid (CSF) have not been previously taken into account in the quantification of APT CEST effects, and correction for the dilution of CEST effects by CSF may allow for more robust measurement of CEST signals. The objective of this study was to compare the robustness of a partial volume (PV) correction model against a standard (4‐pool) multi‐pool model as far as their ability to quantify CEST effects in healthy, normal, and pathological tissue. Methods MRI data from 12 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The number of published clinical studies showed a gradual increase over the years. In the 14 studies, a total of 282 patients had been scanned with APT imaging after accounting for those judged to be duplicate analyses (using the same patient data but for different purposes); the study by Harston et al (33) and two studies by Msayib et al (34,35) (26,(33)(34)(35)(36)(37), three studies involved only acute stroke patients (29,38,39), one study included both hyperacute and acute patients (40), two studies involved acute and early subacute patients (41,42), while two studies involved patients from the hyperacute to early subacute stages (30,43). Further information on these studies such as the treatment received by patients, scanner field strength, radio frequency (RF) saturation scheme, imaging acquisition parameters, image acquisition time, APT effect quantification method, and other MRI sequences acquired, are presented in https://cdn.amegroups.cn/static/public/qims-20-1339-1.…”
Section: Clinical Studies From 2003-2020mentioning
confidence: 99%
See 1 more Smart Citation
“…The number of published clinical studies showed a gradual increase over the years. In the 14 studies, a total of 282 patients had been scanned with APT imaging after accounting for those judged to be duplicate analyses (using the same patient data but for different purposes); the study by Harston et al (33) and two studies by Msayib et al (34,35) (26,(33)(34)(35)(36)(37), three studies involved only acute stroke patients (29,38,39), one study included both hyperacute and acute patients (40), two studies involved acute and early subacute patients (41,42), while two studies involved patients from the hyperacute to early subacute stages (30,43). Further information on these studies such as the treatment received by patients, scanner field strength, radio frequency (RF) saturation scheme, imaging acquisition parameters, image acquisition time, APT effect quantification method, and other MRI sequences acquired, are presented in https://cdn.amegroups.cn/static/public/qims-20-1339-1.…”
Section: Clinical Studies From 2003-2020mentioning
confidence: 99%
“…Six of the included studies involved only hyperacute patients, scanned within 24 hours from onset (26,(33)(34)(35)(36)(37), whereas the other eight studies involved patients that were scanned outside of this time frame (29,30,(38)(39)(40)(41)(42)(43). Among which, three studies investigated the progression of the disease with time, namely the studies by Song et al (40), Yu et al (30), and Momosaka et al (43).…”
Section: Apt Effect In Ischemic Lesionsmentioning
confidence: 99%
“…Recently, there have been several efforts to introduce other approaches for analyzing CEST data, including a three-offsets method [9], extrapolated semi-solid MT model reference approach [10], multiple-pool Lorentzian fitting [11,12] and Lorentzian difference (LD) analysis [13]. However, three-offsets method assumes a simplistic linear baseline, which is limited to high-field application [14]. EMR can achieve higher detection sensitive and allows a reliable delineation of ischemic penumbra tissues [15], however, this method requires longer scanning time.…”
Section: Introductionmentioning
confidence: 99%
“…The amide pool M0 prior mean was 90 mM, with a standard deviation (SD) of 20 mM for the human data and 200 mM for the preclinical data. The multipool model‐based analysis is implemented in Quantiphyse, made available for download at https://www.quantiphyse.org 15,19,37 …”
Section: Methodsmentioning
confidence: 99%
“…The multipool model-based analysis is implemented in Quantiphyse, made available for download at https:// www.quantiphyse.org. 15,19,37 In previous studies MT effects arising from semisolid tissue have been quantified using the model-free conventional MT ratio (MTR) metric, defined as MTR = S 0 −S(50 ppm) S 0…”
Section: Quantification Of Cest Effectsmentioning
confidence: 99%